Origins of alphavirus-derived small RNAs in mosquitoes - Myles, Kevin M.; Morazzani, Elaine M.; Adelman, Zach N. (RNA biology, 2009)
The continual transmission in nature of many arthropod-borne viruses depends on the establishment of a persistent, nonpathogenic infection in a mosquito vector. The importance of antiviral immunity directed by small RNAs in the mechanism by which alphaviruses establish a persistent, nonpathogenic infection in the mosquito vector has recently been demonstrated. The origin of the small RNAs central to this RNA silencing response has recently been the subject of debate. Here we briefly summarize what is known about the mechanism of small RNA-directed immunity in invertebrates, and discuss current models for the viral triggers of this response. Finally, we summarize evidence indicating that alphavirus double-stranded replicative intermediates trigger an exogenous-siRNA pathway in mosquitoes resulting in the biogenesis of virus-derived siRNAs.